2016
DOI: 10.1177/0890334416637594
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Growth of Children in the Peri/postnatal Epigenetic Twins Study (PETS)

Abstract: Results suggest that supplementing with non-breast milk before 4 months of age was associated with an increased BMI, arm circumference, and abdominal circumference at 18 months of age. The mean BMI decreased from 85% to 65% when infants were breastfeeding for 4 to 6 months as compared to breastfeeding for 1 to 3 months. Breastfeeding for 4 to 6 months appeared to protect against the risk of obesity for the children in the PETS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…Plausible mechanisms for the development of adiposity during a sensitive, early window of nutritional exposure include permanent structural changes, such as decreased b cell mass, accelerated cellular aging, telomere shortening with cell division and oxidative damage, and epigenetic programming changes from transcription to protein translation (39,45). Our results suggest that the earliest months of life (,3 mo of cumulative breastfeeding) are a crucial time period during postnatal growth in the development of adipose tissue (38,46,47).…”
Section: Mechanismsmentioning
confidence: 68%
See 1 more Smart Citation
“…Plausible mechanisms for the development of adiposity during a sensitive, early window of nutritional exposure include permanent structural changes, such as decreased b cell mass, accelerated cellular aging, telomere shortening with cell division and oxidative damage, and epigenetic programming changes from transcription to protein translation (39,45). Our results suggest that the earliest months of life (,3 mo of cumulative breastfeeding) are a crucial time period during postnatal growth in the development of adipose tissue (38,46,47).…”
Section: Mechanismsmentioning
confidence: 68%
“…When restricted to full breastfeeding, each additional month of full breastfeeding reduced the risk of overweight by 6%/mo (11), suggesting that exclusivity of breastfeeding is central to the mechanism of protection (38,39). Owen et al (9) concluded that breastfeeding reduces obesity risk compared with formula feeding (OR: 0.87; 95% CI: 0.85, 0.89).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, unadjusted models for the associations between longitudinal postnatal depressive symptoms and child growth (results not shown) were followed by adjusted models of postnatal depressive symptoms on child growth. We additionally adjusted for antenatal depression (yes, no), cigarette smoking during pregnancy (yes, no), alcohol usage during pregnancy (yes, no), gestational diabetes (yes, no), gestational hypertension (yes, no), and breastfeeding at hospital discharge (yes, no), as well as for the confounders listed above. All models were adjusted for the children's age at last assessment of growth.…”
Section: Methodsmentioning
confidence: 99%
“…75 A recent study concluded that the mean body mass index (BMI) decreases from 85 to 65% when infants are breastfed for 4-6 months as opposed to 1-3 months and supplementation with non-breast milk before 4 months of age correlates with an increased BMI, arm circumference, and abdominal circumference at 18 months of age. 80 Breastfeeding may even confer protective effects on offspring obesity in children whose mothers experienced pre-gestational diabetes. 81 Longer duration of breastfeeding may attenuate the risk of obesity in offspring whose mothers experienced excessive gestational weight gain.…”
Section: Obesity and Cardiometabolic Disordersmentioning
confidence: 99%